Prof. dr Stefan CZARNECKI - Committe and Board, Editorial (Archives of Acoustics, 1982)
Stefan Czarnecki (born in 1925) graduated from Gdańsk Technical University in 1949 as an electronic engineer with specialization in acoustics. After several years of work at the Central Laboratory of the Polish Radio and at Warsaw Technical University, in 1953 he began work at the Institute of Fundamental Technological Research of the Polish Academy of Sciences, where in 1957 he became head of the Analogy Department. In 1963 he moved with the Department to the Institute of Automation and returned to the Institute of Fundamental Technological Research in 1974 to become head of the Department of Aeroacoustics.